Spatial Analysis of HIV/AIDS in Pakistan (Bangladesh Journal of Medical Science, 2018)
Background: HIV/AIDS has emerged as a serious worldwide health problem since 1980s and the attainment of a successful disease control program and an effective viral cure is still elusive. Currently, careful estimates put the number of HIV/AIDS affected people at 43 million all over the world. Till such time the disease remains uncured, effective policies are required for the control of HIV/AIDSMethod: The present study is based on the available regional data of recorded HIV/AIDS cases in different provinces of Pakistan.Result: To demonstrate the clustering of infected groups in the target areas we have resorted to the use of Hot Spot assessment and spatial autcorrelation techniques.Conclusion: We conclude that due to a number of socio-economic reasons strong clustering of infection are appearing in a predictable pattern across Pakistan.Bangladesh Journal of Medical Science Vol.17(3) 2018 p.433-438